EFEKTIVITAS METODE COVERING DALAM PENGELOLAN AIR ASAM TAMBANG DI PT. BINUANG MITRA BERSAMA BLOK DUA, KABUPATEN TAPIN, KALIMANTAN SELATAN - Mukhlis Abdi; Idiannor Mahyudin; Fadly H Yusran; Achmad Syamsu Hidayat (EnviroScienteae, 2022)
The formation of AMW is basically unavoidable in mining activities, AMW can be formed in pit and disposal area that are contaminated with potential acid forming material (PAF). The magnitude of the potential impact that AMW can have on mining activities certainly encourages every business actor to conduct a study on various preventive measures that are effectively implemented in AMW management, one of which is covering method. This thesis research aims to analyze the preventive covering method in the management of AMW and its effectiveness in meeting quality standards of liquid waste in coal mining activities. The Object of research is surface water that is in contact with covering treatment area (soil) which is also given additional treatment by planting cover crops and pioneer plants at OPD Sitarum. Surface water quality was tested in the laboratory with reference to BMLC standard of South Kalimantan Governor Regulation Number 36 of 2008. The results of the laboratory tests were then calculated for effectiveness and proved statistical analysis using normality test, homogeneity test, CRD test and DMRT to be able to conclude the effect of covering treatment in the management of AMW. The results showed that the application of covering method in OPD Sitarum was able to have a positive and significant effect on improving surface water quality. Where based on the results of laboratory tests, the SA4 and SA5 treatments have met the BMLC standard of the South Kalimantan Governor Regulation Number 36 of 2008. The laboratory results are strengthened by statistical data which shows that all treatment data are normally distributed and homogeneous, the results of CRD and DMRT analysis show the parameters of pH, TSS, and total-Fe was significantly different between SA2, SA3, SA4, and SA5 treatments against SA1 (control). Meanwhile, total-Mn parameter stated that SA2 and SA3 were not significantly different from the control, SA4 and SA5 were significantly different from the control. And for Cadmium (Cd) parameter, all treatments (SA2, SA3, SA4, and SA5) were not significantly different from the control. The conclusion of this research, the covering method applied in OPD Sitarum is considered effective in the management of AMW in a preventive manner. This is proven in SA4 treatment (covering + cover crop + Pioneer 1-2 years), where the results of the surface water quality test have met the BMLC standards of the South Kalimantan Governor Regulation Number 36 of 2008 with values: pH 6.95; TSS 159 mg L -1 ; total-Fe 1.93 mg L-1 ; total-Mn 0.031 mg L-1 ; and Cd 0.0045 mg L-1 . And the best covering treatment and effectiveness were found in SA5 treatment (covering + cover crop + 3-4 years pioneer plant) with values: pH 6.67; TSS 76.5 mg L-1 (97.22%); totalFe 1.13 mg L-1 (88.71%); total-Mn 0.019 mg L-1 (87.58%); and Cd 0.0058 mg L-1 (8.00%).